2005
DOI: 10.1061/(asce)1090-0241(2005)131:11(1399)
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effects of Tunneling on Existing Pipelines

Abstract: A method is presented for estimating the maximum bending moment for continuous ͑or rigidly jointed͒ pipelines affected by tunnel-induced ground movement. The estimation can be made based on the knowledge of tunnel and pipeline geometries, the stiffness of soil and pipeline, and tunnel-induced ground deformation at the pipeline level. The method takes account of soil nonlinearity by an equivalent linear approach, in which the stiffness of the soil is evaluated based on an average deviatoric strain developed alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 281 publications
(158 citation statements)
references
References 9 publications
3
147
0
8
Order By: Relevance
“…18). In line with the observations of Vorster et al (2005), the method overpredicts the measured maximum bending moments by a factor of 1·9 to 5·1. Better agreement was found for the case of the smaller clear distance between the two tunnels (0·5D) as it resulted in bending strains that were more consistent with the Gaussian profile.…”
Section: Centrifuge Modelling Test Resultssupporting
confidence: 82%
“…18). In line with the observations of Vorster et al (2005), the method overpredicts the measured maximum bending moments by a factor of 1·9 to 5·1. Better agreement was found for the case of the smaller clear distance between the two tunnels (0·5D) as it resulted in bending strains that were more consistent with the Gaussian profile.…”
Section: Centrifuge Modelling Test Resultssupporting
confidence: 82%
“…Fig. 13 compares pile displacements with those based on a modified Gaussian (Vorster et al, 2005) fit to the test G displacements (see Williamson, 2014); also shown in the plots are the LVDT displacements at the locations behind the piles, for comparison with the PIV data. The equivalent subsurface soil settlements predicted by Mair et al (1993) and Rankin (1988) are also shown as both models are used to predict open-face tunnelling movement.…”
Section: Comparison With 'Greenfield' Settlements and Analytical Modementioning
confidence: 99%
“…Because relatively small horizontal strains are transferred to buildings [24,25,28], for each building we selected PS cross sections localized on the roof and projected them onto the vertical. We interpolated the PS points using a modified Gaussian model [46,47] (Figure 4) and calculate the ∆/L values (see Figure 2). We derived the sagging and hogging modification factors by dividing these values by the corresponding (∆ gr /L gr ), obtained through fitting the PLP data with an appropriate Gaussian curve, as illustrated in Figure 3.…”
Section: Resultsmentioning
confidence: 99%